Osthole ameliorates wear particle-induced osteogenic impairment by mitigating endoplasmic reticulum stress via PERK signaling cascade - Xin Yu; Juan Jiang; Cheng Li; Yang Wang; Zhengrong Ren; Jianlun Hu; Tao Yuan; Yongjie Wu; Dongsheng Wang; Ziying Sun; Qi Wu; Bin Chen; et al. (Molecular Medicine)
Abstract Background Periprosthetic osteolysis and subsequent aseptic loosening are the leading causes of failure following total joint arthroplasty. Osteogenic impairment induced by wear particles is regarded as a crucial contributing factor in the development of osteolysis, with endoplasmic reticulum (ER) stress identified as a key underlying mechanism. Therefore, identifying potential therapeutic targets and agents that can regulate ER stress adaption in osteoblasts is necessary for arresting aseptic loosening. Osthole (OST), a natural coumarin derivative, has demonstrated promising osteogenic properties and the ability to modulate ER stress adaption in various diseases. However, the impact of OST on ER stress-mediated osteogenic impairment caused by wear particles remains unclear. Methods TiAl6V4 particles (TiPs) were sourced from the prosthesis of patients who underwent revision hip arthroplasty due to aseptic loosening. A mouse calvarial osteolysis model was utilized to explore the effects of OST on TiPs-induced osteogenic impairment in vivo. Primary mouse osteoblasts were employed to investigate the impact of OST on ER stress-mediated osteoblast apoptosis and osteogenic inhibition induced by TiPs in vitro. The mechanisms underlying OST-modulated alleviation of ER stress induced by TiPs were elucidated through Molecular docking, immunochemistry, PCR, and Western blot analysis. Results In this study, we found that OST treatment effectively mitigated TiAl6V4 particles (TiPs)-induced osteolysis by enhancing osteogenesis in a mouse calvarial model. Furthermore, we observed that OST could attenuate ER stress-mediated apoptosis and osteogenic reduction in osteoblasts exposed to TiPs in vitro and in vivo. Mechanistically, we demonstrated that OST exerts bone-sparing effects on stressed osteoblasts upon TiPs exposure by specifically suppressing the ER stress-dependent PERK signaling cascade. Conclusion Osthole ameliorates wear particle-induced osteogenic impairment by mitigating endoplasmic reticulum stress via PERK signaling cascade. These findings suggest that OST may serve as a potential therapeutic agent for combating wear particle-induced osteogenic impairment, offering a novel alternative strategy for managing aseptic prosthesis loosening.